Investigation and optimization of battery thermal management system based on composite phase change material and variable wall liquid cooling plate - Xiaoyong Gu; Wenbo Lei; Jiacheng Xi; Mengqiang Song (International Journal of Thermofluids)
To mitigate the risk of thermal runaway in lithium-ion batteries, an efficient battery thermal management system (BTMS) assumes paramount importance. A BTMS based on composite phase change material (CPCM) and variable wall liquid cooling plate (LCP) is proposed in this research. The numerical model of the BTMS was established and experimentally validated. The influence of the wall of LCP on battery temperature was investigated, and the efficiency of phase change material (EOP) index was proposed to assess the efficacy of CPCM. The genetic algorithm was employed to optimize the structure of the CPCM, and the influence of flow rate on the maximum temperature of the battery pack was studied. The results demonstrate a reduction of 1.81 °C in the maximum temperature of the battery pack upon implementation of the variable wall LCP. The optimized EOP achieves a value of 0.07 °C/g, resulting in a temperature difference of 0.56 °C. Furthermore, maintaining the maximum temperature of the battery pack below 40 °C only requires a water flow rate greater than 0.89 g/s. These results can serve as a valuable reference for the development of battery thermal management systems utilizing CPCM and liquid-cooling.